Influence of Workplace Environment and Participative Decision- Making on Job Loyalty of Banking Employees: Determining the Mediating Role of Job Satisfaction - Farhan Sarwar; Tehreem Anjum; Bilal Abassi (Journal of Applied Research and Multidisciplinary Studies, 2023)
The current study attempted to discuss the significance of employee loyalty and its impact on a company's success. Employee loyalty plays an essential role for low turnover rates, enhanced productivity, and improved customer service. The current study aimed to explore the mediating role of job satisfaction and employee loyalty in the banking sector in Pakistan's service industry. A survey was conducted to gather the data from the banking sector which constituted population of this study. The statistics were investigated by using SPSS and Smart PLS. By analyzing the data, the study established that participative decision-making is positively related to job satisfaction, whereas workplace environment has an insignificant relationship with job satisfaction. Additionally, job satisfaction was found to be a significant intervening variable with a positive relationship to employee loyalty. The findings revealed that when employees experience high levels of satisfaction with their work, they are far more inclined to exhibit firm loyalty to their employers. The current paper explored factors, such as a supportive work environment and fair compensation that contribute to employee loyalty. Moreover, it also investigated the role of job satisfaction and identified intrinsic and extrinsic factors influencing loyalty and commitment. The study also highlighted the crucial role played by employee loyalty to determine a company's success. Organizations should recognize that fostering employee loyalty leads to several benefits. At the same time, it also establishes job satisfaction as a mediating factor between participative decision-making and employee loyalty, highlighting the fact that employees who have a significant level of job satisfaction are more inclined to demonstrate strong loyalty towards their employers.